A CONTENT ANALYSIS ON LISTENING MATERIALS IN ENGLISH TEXTBOOK BASED ON 2013 CURRICULUM FOR THE TENTH GRADE STUDENTS AT SENIOR HIGH SCHOOL 04 BENGKULU CITY - Okta Romania, Yosi; Hosen, Riswanto; Martina, Feny (JPT : Jurnal Pendidikan Tematik, 2022)
This research focused on listening material in English Textbooks published by Private Publications/Erlangga based on the 2013 Curriculum syllabus and this study aims to determine whether the listening material in English Textbooks for Tenth Grade Students of SMAN 04 Bengkulu City meets the aspects of the curriculum syllabus. 2013. This research is very important for the academic world to make it easier for a student and teacher to choose a good textbook. The method used in this research is Content Analysis. Researchers used two analysis matrices in collecting data. The first analysis matrix will show the listening material in the textbook with the 2013 curriculum syllabus. The second analysis matrix will show the percentage score of the English textbook based on the criteria from the 2013 curriculum. As for the results of the data analysis, the first matrix shows that the listening material in the English textbook is appropriate with the 2013 curriculum syllabus and the second matrix also shows that English textbooks are in the "good" category where textbooks published by Private Publications/Erlangga have an average percentage of 92% (Good). In conclusion, English textbooks published by Private Publications/Erlangga are in the “good” category for students in carrying out the teaching and learning process.